Long-term disease stability with bicalutamide in a man with aggressive angiomyxoma: case report and state of art - Franza, Andrea; Gusmaroli, Eleonora; Fabbroni, Chiara; Vigorito, Raffaella; Pasquali, Sandro; Casali, Paolo Giovanni; Sanfilippo, Roberta Giovanna (Frontiers in Oncology, 2024)
Aggressive angiomyxoma (AA) is a rare mesenchymal neoplasm, which is commonly diagnosed in females and located in the perineal and pelvic region. Tissue specimens of AA patients often show positivity for estrogen (ER) and progesterone receptors (PgR), while some cases of androgen receptor (AR) positivity have been reported in males. When feasible, surgical excision represent the most effective treatment of AA; however, when experiencing advanced or recurrent disease, local disease control could be achieved with systemic hormonal treatment. To date, evidence regarding AA management in male patients is scarce, and only a few cases have been reported in literature. Hereby, we describe the case of a 59-year-old-man suffering from perineal AA with positivity for androgen receptors (AR) showing a long-lasting disease stability during the treatment with an AR-blocking drug (bicalutamide). A literature review regarding the state of art of AA management with a particular look to male patients is also provided.